A Review of Banana Fiber: Impact of Treatment, Filler Materials, Hybrid Composite, and Application - Al Ichlas, Imran; Jenny, Delly; Samhuddin, .; Janviter, Manalu; Johni Jonathan, Numberi; Apolo, Safanpo (INTI International University, 2023)
This review paper examines the significance of comprehending the attributes of banana fibers and their initial processing in influencing the mechanical, thermal, and morphological aspects of composites. The study's findings indicated that the application of alkaline solutions or other chemicals to banana fibers had a substantial influence on the performance of the composite material. Modifications in fiber treatment parameters have the potential to modify composite characteristics, such as the interplay between fibers and matrix. Incorporating filler elements significantly affects the composite by enhancing its rigidity and grip while also altering physical characteristics like heat conduction and resistance to corrosion. The utilization of banana fiber components, in conjunction with other fiber and filler materials, showcases ingenuity in creating sustainable composites for various industrial applications. The study emphasizes the necessity of creating more robust, less weighty, and ecologically conscious composites across several industrial domains. The study also emphasizes the potential of banana's fiber-enhancing composites in several industries, such as automotive, construction, aerospace, electronics, and sports.